2022
DOI: 10.1039/d1tb02620h
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophilic edge-rich graphene for the simultaneous and disposable sensing of dopamine, ascorbic acid, and uric acid

Abstract: A simple and rapid simultaneous sensing strategy of multiple biomarkers is of great importance but challenging in health diagnosis. In this study, a novel free-standing edge-rich graphene film (fs-ERG) was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Hydrophilicity/hydrophobicity, as a typical surface characteristic of material, has shown great superiority in electrochemical fields. , For one thing, the surface wettability directly affects the electrochemical activities of materials as well as the microenvironment of reactive interfaces . For example, our group has reported that the hydrophilicity/hydrophobicity surfaces of metal and carbon showed enhanced electrocatalysis and electrochemical biosensing. , And for another, the hydrophobicity or hydrophilicity induces a cascade activation of intracellular proteins and genes expression, and determines cells biological behaviors, like adhesion, migration, proliferation, and differentiation in vitro. , For instance, an amphiphilic peptide including a hydrophobic region for self-assembly, a flexible linker, and a hydrophilic region served as a ligand to specifically bind integrin on the cells was used for sensitive analysis of tumor cells . Therefore, the surface hydrophilicity/hydrophobicity regulation of the electrode material would pave a noteworthy avenue for real-time monitoring of electroactive cells secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophilicity/hydrophobicity, as a typical surface characteristic of material, has shown great superiority in electrochemical fields. , For one thing, the surface wettability directly affects the electrochemical activities of materials as well as the microenvironment of reactive interfaces . For example, our group has reported that the hydrophilicity/hydrophobicity surfaces of metal and carbon showed enhanced electrocatalysis and electrochemical biosensing. , And for another, the hydrophobicity or hydrophilicity induces a cascade activation of intracellular proteins and genes expression, and determines cells biological behaviors, like adhesion, migration, proliferation, and differentiation in vitro. , For instance, an amphiphilic peptide including a hydrophobic region for self-assembly, a flexible linker, and a hydrophilic region served as a ligand to specifically bind integrin on the cells was used for sensitive analysis of tumor cells . Therefore, the surface hydrophilicity/hydrophobicity regulation of the electrode material would pave a noteworthy avenue for real-time monitoring of electroactive cells secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of materials have been applied for sensing development, including metallic origin materials such as Pt, [4] Al2O3, [5] MgO, [6,7] TiO2, [8] Au-SiO2 nanocomposites; [9] carbon derivative materials like carbon powder, [10] graphene, [11][12][13] carbon nanotubes, [14][15][16] and combination of them. [17][18][19] Because of its inherent properties, such as its nano-2D structure and excellent mechanical and electrical properties, graphene is one of the most promising candidates.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Because of its inherent properties, such as its nano-2D structure and excellent mechanical and electrical properties, graphene is one of the most promising candidates. [11][12][13] Besides fabricating graphene material for the sensor, the electrode fabrication process plays a very important role in creating a stable electrode with high sensitivity and repeatability. However, the large 2D size is challenging, especially when using expensive chemical vapour deposition (CVD) and molecular beam epitaxy (MBE) methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations